Pengaruh Intesitas Bermain Game Online Terhadap Prokrastinasi Akademik Pada Mahasiswa: The Effect of Intensity of Playing Online Games on Academic Procrastination in College Students - Waskitho Jati; Lely Ika Mariyati (Universitas Muhammadiyah Sidoarjo, 2025)
This study examines the relationship between online gaming intensity and academic procrastination among university students. General Background: Academic procrastination is a persistent behavioral issue in higher education that may reduce academic performance and psychological well-being. Specific Background: The increasing engagement of students in online gaming activities raises concerns regarding time management and academic responsibility. Knowledge Gap: Although prior studies have explored procrastination and digital behavior, differences in research subjects, variables, and settings indicate the need for contextual empirical evidence among psychology students in Indonesia. Aims: This study aims to analyze the role of online gaming intensity in predicting academic procrastination among students of the Faculty of Psychology and Education at a private university in Sidoarjo. Results: Using a quantitative correlational design with 399 participants and simple linear regression analysis, the findings reveal a positive and statistically significant relationship (B = 0.571; β = 0.593; p < 0.001), indicating that higher gaming intensity is associated with higher levels of academic procrastination. Novelty: The study provides localized empirical evidence by focusing on psychology students and applying regression analysis to quantify predictive contribution. Implications: The findings underline the importance of time management, self-control, and digital literacy programs to prevent maladaptive academic behavior in higher education contexts. Keywords: Academic Procrastination, Online Gaming Intensity, University Students, Digital Behavior, Time Management Key Findings Highlights: Higher gaming frequency and duration are associated with increased task delay tendencies. Statistical modeling confirms a significant predictive contribution of digital engagement toward task postponement. Preventive strategies involving self-regulation and structured scheduling are recommended within campus settings.